Association of candidate genes and molecular markers with male reproductive traits and meat quality properties in boer and boer cross goats - Nikbin, Saeid (2013)
Boer goats are popularly reared in Malaysia as pure breed or as crosses with the local goat populations. As such, identification of the factors influencing their meat production and reproduction is necessary in order to design optimal breeding and selection programs. Conventional selection methods are usually costly for traits which are expressed later in life and evaluated in adulthood, and may be inappropriate when animals need to be sacrificed for such evaluation to be carried out. Using candidate genes in the selection criteria for male reproduction traits may allow early selection thus decreasing the rearing cost, decrease generation interval and increase accuracy of selection. It is more important in the selection for meat quality traits as animals need not be slaughtered to confirm their genetic merit for these traits, thus making them available for breeding. This study aimed to identify and elucidate the effects of functional candidate genes as well as non genetic factors on meat and semen quality traits in Boer goats and Boer crosses. This objective was accomplished through two independent studies. In the first study, fresh and thawed 1-day and 6-month frozen semen from 36 Boer bucks and 17 Boer crosses were evaluated. The semen quality traits were analyzed for the effects of fixed factors and 17 candidate genes chosen based on their physiological or biological functions. The effects of age, population,cryopreservation period and some of their interactions on the semen quality traits were significant (P<0.05). Sperm motility and average velocity were 44.16 % and 96.35 μm/s, respectively, after cryopreservation for 1 day, and 37.61 % and 90.04 μm/s, respectively, after 6 months. The younger goats showed higher sperm motility (43.32 %) for fresh and (38.45 %) for post-thaw semen after six months than older bucks. Restriction fragment length polymorphism (PCR-RFLP) and single strand conformation polymorphism (SSCP) analysis and comparative sequencing revealed three single nucleotide polymorphisms (SNP) in exon 3 of follicle stimulating hormone beta (FSHB), 200A>G (FSHB3-1), 226T>C (FSHB3-2) and 237A>G (FSHB3-3); two SNPs in the coding region of heat shock protein 70 (HSP70),73A>C (HSP70-1) and 190C>G (HSP70-2); one SNP in exon 2 of Luteinizing hormone beta (LHB) (207T>C) (LHB2); and one SNP in 5‘-UTR of neuropeptide Y (NPY) (182G>T) gene. There was also an indel in position 29 of NPY3. Analyses of variance revealed significant association of the candidate genes with libido and semen quality traits. The three SNPs of FSHB3 had significant effect on libido (P<0.05), progressive motility and abnormality of fresh semen (P < 0.05), and on motility, velocity and viability traits of post-thaw semen (P < 0.05). The SNPs of HSP70 were associated with libido, semen volume (VOL), sperm concentration (SCON), motility traits and sperm viability of fresh semen (P<0.05) and with motility and viability traits of post-thaw semen (P<0.05). The two SNPs of NPY gene influenced libido (P<0.05), progressive motility (PROG) of fresh semen (P<0.05), and motility traits, velocity traits, amplitude lateral sperm head (ALH), straightness (STR), linearity (LIN) and acrosome integrity (ACI) of post-thaw semen (P<0.05). In the second study, carcass characteristics and meat quality traits of 30 Boer goats,which were either not transported or transported in low or high stocking density before slaughter, were evaluated. The effects of non genetic factors and 24 candidate genes chosen for their known physiological or biological functions were investigated. The effects of aging, transportation and muscle types and their interactions were significant on meat quality traits (P<0.05). The transported goats showed a significant (P<0.05) decrease in meat pH and tenderness at Day 0. Aging caused a drop of pH and increased meat tenderness. PCR-RFLP (restriction fragment length polymorphism) and sequencing analysis revealed one SNP in growth hormone (GH) gene, and two SNPs in the coding region of HSP70 gene, 73A>C (HSP70-1) and 190C<G (HSP70-2); and two SNPs in the coding region of HSP27b, 119T>C (HSP27b-1) and 132C>G (HSP27b-2). Analyses of variance showed significant association of GH4-HaeIII with carcass dressing percentage (P < 0.05); the two SNPs of HSP70 were associated with pH, glycogen content, drip loss, cooking loss,redness (a*) and chroma (P<0.05); while the two SNPs of HSP27b-1 were associated with calpastatin level and drip loss shear force (P<0.05). The results of the present study shows there are candidate genes associated with semen quality as well as carcass and meat quality traits of Boer goats and Boer crosses. These genes may be targeted and used in marker assisted selection for the respective traits to improve the production and reproduction performance of the animals.